2014
DOI: 10.1097/aco.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia in patients with pre-existing neurologic disease

Abstract: Regional anesthesia can be safely utilized in patients with pre-existing neurological disease and may have benefits over general anesthesia; however, a conservative approach is warranted. In addition, further publications regarding regional techniques in this population are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 61 publications
0
17
0
6
Order By: Relevance
“…(1-4) Si bien en algunos casos se ha reportado prolongación del tiempo de bloqueo. (4,5) Es desconocido el mecanismo por el que la alteración axonal en pacientes con ECMT se puede ver afectada por exposición directa a los anestésicos locales. (4) No obstante, se asume que tienen mayor susceptibilidad a los mismos debido a disminución y, en algunos casos, ausencia de mielina.…”
Section: Discussionunclassified
“…(1-4) Si bien en algunos casos se ha reportado prolongación del tiempo de bloqueo. (4,5) Es desconocido el mecanismo por el que la alteración axonal en pacientes con ECMT se puede ver afectada por exposición directa a los anestésicos locales. (4) No obstante, se asume que tienen mayor susceptibilidad a los mismos debido a disminución y, en algunos casos, ausencia de mielina.…”
Section: Discussionunclassified
“…Few studies regarding safety in neuraxial and peripheral blocks in these patients can be found, the majority of them are obstetric case reports [11,12]. The risks of regional anesthesia in patients with neurofibromatosis rely basically on 2 major concerns: a theoretical spread of tumor cells and, most importantly, bleeding caused by manipulation of these tumors [4,11,12]. Therefore, those studies recommend a thorough neurological examination to discard possible previous alterations or intracranial and neuraxial tumors prior to regional anesthesia management [4,11,12] and after the surgery also a thorough neurological examination to ensure that the patient has returned to his preexisting neurologic status [3] and the documentation of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Neurofibromatosis affects every major anatomical system and brings for the anesthesiologist important issues related, most importantly, to potential airway difficulty, tumors affecting peripheral nerves, and neuraxial or intracranial tumors [3,4]. In the following case we discuss a patient with neurofibromatosis type 1 admitted for an open thoracotomy surgery for pulmonary tumor resection and the option for an alternate analgesic technique.…”
Section: Introductionmentioning
confidence: 99%
“…In all cases where regional anesthesia is considered, the benefits must be weighed against potential complications; the greatest risk being a new or worsened neurologic deficit. With the advancement of regional techniques paired with ultrasound guidance, literature suggests that belonging to this patient population should not necessarily be a contraindication to regional anesthesia [2]. Due to the medicolegal concerns and historic avoidance of regional anesthesia in patients with neurologic disorders, there is a lack of discussion and studies in the United States on this topic.…”
mentioning
confidence: 99%